2020
DOI: 10.31557/apjcp.2020.21.2.531
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Attitudes Towards Clinical Pharmacy Services and Their Impact on The Management of Cancer in Taif, Saudi Arabia

Abstract: Aim: To assess the perception and attitude of HCPs and health-related science colleges' students regarding the clinical pharmacists' roles and responsibilities in providing better pharmaceutical care to patients in Taif, Saudi Arabia and to detect its impact on management of cancer. Methods: This study was conducted in four randomly selected hospitals in Taif and three health-related science colleges in Taif University. A questionnaire was distributed to HCPs and another questionnaire to students of health-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…This result is in line with Samarghandian et al [45] These cytokines were significantly reduced in candesartan or EGCGtreated groups. These outcomes are in accordance with others which reported the impact of candesartan on proinflammatory markers [46,47] ;…”
Section: Discussionsupporting
confidence: 93%
“…This result is in line with Samarghandian et al [45] These cytokines were significantly reduced in candesartan or EGCGtreated groups. These outcomes are in accordance with others which reported the impact of candesartan on proinflammatory markers [46,47] ;…”
Section: Discussionsupporting
confidence: 93%
“…National level studies showed that pharmacists play an important role on the healthcare team. 40 Studies also revealed that pharmacists performed a major role in detecting and preventing prescribing errors and medication errors, increasing patient compliance with treatment, performing medication reconciliation, providing patient counselling and playing a key role in raising public health awareness. [41][42][43]…”
Section: Dg 11-impact and Outcomesmentioning
confidence: 99%
“…17,18 The perception of physicians towards clinical pharmacists or towards themselves has been studied extensively in the Arab region and across the world. 17,[19][20][21][22][23][24][25][26][27][28] Abdel-Latif had noted that in the Arab region, physicians' acceptance of the clinical pharmacist's role in clinical practice remains debatable. 31 This may be due to the fact that the current roles of clinical pharmacists have not been clearly established and agreed.…”
Section: Introductionmentioning
confidence: 99%